CLASSIFICATION OF CONTENTS OF GEOSCIENSE IN SECONDARY CURRICULA IN GREECE, 1830 -2015 - Makri, K.; Pavlides, S. (Bulletin of the Geological Society of Greece, 2016)
The educational systems are evolving dynamically reflecting social and economical changes. The Geology has developed and evolved in Greece, based on specific economic and social interactions. This paper attempts to define and interpret the position of the teaching of geosciences in Greek Secondary Education, from 1830 until today, with reference to the educational changes and their historical and social context.